Implementation of Social Media Efforts to Increase Sales at PT. Fertilizer Sriwidjaja Palembang - Simanjuntak, Robetama; Helmi, Sulaiman; Trisninawati, Trisninawati (Formosa Journal of Multidisciplinary Research, 2024)
This research delves into the assessment of social media implementation at PT Fertilizer Sriwidjaja Palembang, with a specific focus on the TikTok, Instagram, and YouTube platforms. The study aims to discern the influence of these platforms on brand awareness, product sales, and consumer behavior. Utilizing interviews, observations, and qualitative data analysis, the findings reveal that TikTok plays a substantial role in elevating both brand awareness and sales. Meanwhile, Instagram emerges as an effective platform for comprehensive product introduction, and YouTube introduces an innovative dimension through the creation of compelling content. This study sheds light on the multifaceted impact of social media platforms on various aspects of business at PT Fertilizer Sriwidjaja Palembang.